BUDDHISM AND IMPERIAL AUTHORITY UNDER WU ZETIAN: INSTITUTIONALISING THE SANGHA AS POLITICAL STATECRAFT IN EARLY TANG CHINA - Yiran WEN; Chompoo Gotiram (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study investigates how Empress Wu Zetian (r. 690–705 CE), China's only female emperor, strategically restructured the Buddhist Sangha to consolidate imperial authority in the early Tang period. While earlier scholarship often emphasizes Wu's use of Buddhist prophecy and personal devotion, this article foregrounds the administrative and institutional transformations that embedded Buddhism within statecraft. Drawing on primary sources—including imperial edicts in the Jiu Tang shu and Xin Tang shu, Dunhuang manuscripts, monastic biographies, and apocryphal scriptures such as the Great Cloud Sutra—the analysis reconstructs how the Sangha was bureaucratised through monk-official appointments, ordination examinations, and temple registration, and how its economic base expanded through land endowments and fiscal privileges. Theoretically, the article integrates Max Weber's model of charismatic and routinized legitimacy with Pierre Bourdieu's concept of religious capital to conceptualise Buddhist institutions as both ideological producers and administrative instruments. Findings reveal that Wu Zetian's mobilisation of Buddhism was not only a strategy of female legitimation in a Confucian patriarchal order, but also a catalyst for the centralisation of Tang religious governance. This case thus contributes to broader debates on religion and state formation, the political uses of Buddhist institutionalisation, and the gendered dynamics of religious legitimacy in imperial China.